Sexually Transmitted Infections, Sexual Behavior, and The HIV/AIDS Epidemic* - Oster, Emily (Quarterly Journal of Economics, 2005)
Forty million people are infected with HIV worldwide; twenty-five million of them are in Sub-Saharan Africa. This paper addresses the question of why Africa has been so heavily affected by HIV, and what explains the variation within Africa. I present a model that decomposes epidemic level into differences in sexual behavior and differences in viral transmission rates. I argue, using evidence drawn from the existing medical literature, that Africa has very high HIV transmission rates, likely due to high rates of other untreated sexually transmitted infections. The difference in transmission is large enough to explain the observed difference in prevalence between the United States and Sub-Saharan Africa. The model also provides a good fit to cross-country data within Africa and suggests that, in contrast to the intra-continental results, differences within that continent can be attributed to differences in sexual behavior and epidemic timing. The results suggest that cost-effective policy interventions would focus on decreasing transmission rates within Africa, possibly by treating other untreated sexually transmitted infections.